Study the Effect of Animal Manure, Nitrogen and Phosphorus on Growth, Yield and Yield Components Traits of Mungbean - Sarvari, Basir Ahmad; Nahiz, Aimal; Malakzai, Mohammad Yar; Wasifhy, Mohammad Khan (Journal for Research in Applied Sciences and Biotechnology, 2024)
The field experiment was conducted to assess the effect of different fertilizers sources such as animal manure (AM), Nitrogen (N) and Phosphorus (P) fertilizers on growth, yield and yield components of Mungbean (Vigna radiate L.) during 2019 The applied levels of mentioned sources were (0, 30 ton ha1), (0, 25 & 50 N kg ha-1) and 0, 50 & 70 P kg ha-1) respectively. The experiment was laid out at the research farm of, Badghis University in factorial split-plot design (SPD) with 3 replications. Each replication consisted of (18) plots with (2m x 2m) size. Animal manure was applied to the main plots while, N and P fertilizers were applied to the subplots of the experiment. The results revealed that, animal manure significantly affected all characteristics of Mungbean except total dry matter, yield, and harvest index. The Interactive effect of nitrogen and phosphorus fertilizers was found significant for all characteristics of Mungbean, while the interactive effect of AM x N and AM x P was found non-significant for recorded parameters.